2014
DOI: 10.17660/actahortic.2014.1058.43
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prohexadione Calcium on Vegetative and Reproductive Development in Sweet Cherry Trees

Abstract: Cherry trees display vigorous upright growth, which tends to reduce precocity, flower bud formation and fruit quality. Three trials were performed in the 2010-2011 season on mature 'Lapins' and 'Sweetheart' sweet cherry trees in the Angol area (37°48'50"S, 72°37'36"W). The effects of prohexadione calcium (P-Ca) on shoot growth, leaf area, yield, fruit quality and flower differentiation were assessed. Two rates were evaluated (150 mg L-1 and 250 mg L-1), which were sprayed when shoots were 15 cm long and 15 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
4
8
0
Order By: Relevance
“…This study indicates that under Southern Ontario climatic conditions, P-Ca can markedly decrease the vegetative shoot growth of sweet cherry trees on rootstocks that promote medium-high to high vigor. This is consistent with the results of past experiments conducted in Summerland, BC (Guak et al 2005), Poland (Jacyna and Lipa 2010;Jacyna et al 2012), Chile (Cares et al 2014), and the Pacific Northwest region of the USA (Elfving et al 2003(Elfving et al , 2004(Elfving et al , 2005.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study indicates that under Southern Ontario climatic conditions, P-Ca can markedly decrease the vegetative shoot growth of sweet cherry trees on rootstocks that promote medium-high to high vigor. This is consistent with the results of past experiments conducted in Summerland, BC (Guak et al 2005), Poland (Jacyna and Lipa 2010;Jacyna et al 2012), Chile (Cares et al 2014), and the Pacific Northwest region of the USA (Elfving et al 2003(Elfving et al , 2004(Elfving et al , 2005.…”
Section: Discussionsupporting
confidence: 92%
“…As P-Ca degrades within a matter of weeks following its application (Evans et al 1999), there was likely very little or none of the pre-bloom P-Ca remaining in the shoots that received this treatment by the time they began to grow actively. Similar observations have also been made with P-Ca applications made either after harvest (Cares et al 2014) or in the fall (Manríquez et al 2005). Due to the low persistence of P-Ca, these observations support limiting the application of P-Ca to the period in which shoots are in active growth.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Present findings revealed that ProCa was effective in controlling vegetative growth of cherry trees. Complying with the current findings, a decrease was reported in vegetative growth with ProCa treatments in apples [Greene 1999;Unrath 1999], pears [Basak and Rademacher 2000;Costa et al 2001Costa et al , 2004Elfving et al 2002Elfving et al , 2003Rademacher et al 2004;Smit et al 2005;Asin et al 2007] and cherries [Manríquez et al 2001;Elfving et al 2003;Guak et al 2005;Jayna et al 2012;Cares et al 2014]. Such a decreasing effect of ProCa on vegetative growth may be attributed to inhibition of gibberellin synthesis promoting cell elongation.…”
Section: Discussionsupporting
confidence: 83%